Anti-inflammatory agents reduce microglial response, demyelinating process and neuronal toxin uptake in a model of encephalopathy produced by Shiga Toxin 2 - Pinto, Alipio (2018)
Fil: Pinto, Alipio. Universidad de Buenos Aires. Facultad de Medicina. Instituto de Fisiología y Biofísica "Houssay". Laboratorio de Neurofisiopatología; Argentina.